Generation of Thiyl Radicals from Air-Stable, Odorless Thiophenol Surrogates: Application to Visible-Light-Promoted C–S Cross-Coupling - Swan, Charlie; Maggi, Lorenzo; Park, Mahri; Taylor, Sophie; Shepherd, William; Ball, Liam T. (Synthesis, 2022)
The synthetic versatility of thiophenols is offset by their air-sensitivity and foul odor. It is demonstrated that S-aryl isothiouronium salts can be used as precursors to thiyl radicals, extending the practical benefits of these air-stable, odorless salts from ionic to single electron manifolds. The isothiouronium salts are accessed via Ni-catalyzed cross-coupling of (hetero)aryl iodides and thiourea and are isolated as free-flowing solids following anion exchange. Judicious choice of a redox-innocent counteranion enables use of these convenient thiophenol surrogates in radical processes, as is exemplified by the synthesis of non-symmetrical diaryl thioethers via light-promoted S-arylation.
Keywords: thiophenols; nickel catalysis; C–S cross-coupling; photochemistry; electron donor–acceptor complexes; thiyl radicals; diaryl sulfides